Decision-Making Dysfunctions of Counterfactuals in Depression: Who Might I have Been? - Howlett, Jonathon R.; Paulus, Martin P. (Frontiers in Psychiatry, 2013)
Cognitive neuroscience enables us now to decompose major depressive disorder into dysfunctional component processes and relate these processes to specific neural substrates. This approach can be used to illuminate the biological basis of altered psychological processes in depression, including abnormal decision-making. One important decision-related process is counterfactual thinking, or the comparison of reality to hypothetical alternatives. Evidence suggests that individuals with depression experience exaggerated emotional responses due to focusing on counterfactual decision outcomes in general and regret, i.e. the emotion associated with focus on an alternative superior outcome, in particular. Regret is linked to self-esteem in that it involves the evaluation of an individual’s own decisions. Alterations of self-esteem, in turn, are a hallmark of depression. The literature on the behavioral and neural processes underlying counterfactual thinking, self-esteem, and depression is selectively reviewed. A model is proposed in which unstable self-representation in depression is more strongly perturbed when a different choice would have produced a better outcome, leading to increased feelings of regret. This approach may help unify diverse aspects of depression, can generate testable predictions, and may suggest new treatment avenues targeting distorted counterfactual cognitions, attentional biases toward superior counterfactual outcomes, or increased affective response to regretted outcomes.